De novo designed lactoferrin–oleic acid-loaded chitosan nanoparticles with improved activity and selectivity toward four human cancer cells as compared to conventional complexes - Nawal Abd EL-Baky, Marwa Mohamed Abu-Serie, ELRashdy Moustafa Redwan (Journal of Applied Pharmaceutical Science, 2021)
A correction has been published: Corrigendum to “De novo designed lactoferrin–oleic acid-loaded chitosan nanoparticles with improved activity and selectivity toward four human cancer cells as compared to conventional complexes”. J Appl Pharm Sci. 2025;15(05):254–256. http://doi.org/10.7324/JAPS.2025.110307.corrigendumConsidering the oleic acid (OA) adverse effects on normal and cancer cells besides the less significant anticancer activities of free lactoferrins, this study aimed to formulate camel lactoferrin–OA or human lactoferrin–OA complexes-loaded chitosan nanoparticles that achieved cytotoxicity and apoptotic effect on four human cancer cells (Hela, HepG- 2, Caco-2, and MCF-7) while sparing normal healthy WI-38 cells. Cytotoxicity of these de novo nanoformulations was detected by the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Their apoptotic effect was assessed using multiple staining; acridine orange, ethidium bromide, propidium iodide (PI), and annexin V besides the immunocytochemical nuclear staining protocol for Ki-67, Bcl-2, and p53. The increment in reactive oxygen species (ROS) manufacture was determined in treated cancer cell lines. Contrary to their corresponding complexes, nanocomplexes showed half maximal inhibitory concentrations (IC50) against tumor cells that were significantly (p < 0.05) lower than their safe doses (concentration achieving 100% cell viability, EC100) against WI-38, indicating their selective targeting of tumor cells. The nanoformulated complexes were more effective at inducing apoptosis and ROS increase in tumor cells than their corresponding complexes. A significant decrease in the levels of Ki-67 and Bcl-2 was found, while p53 level was increased in nanocomplexes-treated cancer cells. These findings suggest that nanoformulation of lactoferrin and OA potentiates their activity and selectivity toward cancer cells.
Keywords: Anticancer, camel and human lactoferrins, nanocomplexes, oleic acid.